REMARKS ON DISCIPLINARY LIABILITY OF A RETIRED JUDGE. SELECTED COMPARATIVE CONSIDERATIONS - StÄ™pieÅ„-ZaÅ‚ucka, Beata (Novos Estudos Jurídicos, 2019)
The problems of the judiciary, in some countries, seem to have recently become an important dilemma of constitutional law. One such issue is the issue of retired judges, who at the end of their judicial careers still remain judges, but in a retired state. This raises a wide range of issues, including the proper conduct and behaviour of such judges. Under the rules of many countries in force in this area, such judges are still subject to what is termed disciplinary responsibility and may be held liable for offences committed outside the service, as well as for those committed in the course of the service. The author looks at these solutions and tries to present a model of retired judges’ liability.